2022
DOI: 10.3390/cells11071089
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-Associated Cell Transition and Interaction (SACTAI): A Proposed Mechanism for Tissue Aging, Repair, and Degeneration

Abstract: Aging is a broad process that occurs as a time-dependent functional decline and tissue degeneration in living organisms. On a smaller scale, aging also exists within organs, tissues, and cells. As the smallest functional unit in living organisms, cells “age” by reaching senescence where proliferation stops. Such cellular senescence is achieved through replicative stress, telomere erosion and stem cell exhaustion. It has been shown that cellular senescence is key to tissue degradation and cell death in aging-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…Although aging is not the cause of many neurodegenerative diseases, it can aggravate them because of cellular senescence. Cellular senescence can occur at any life stage, from embryo to adulthood, although it is associated with the aging process [133].…”
Section: Neurodegenerative Diseases In Agingmentioning
confidence: 99%
“…Although aging is not the cause of many neurodegenerative diseases, it can aggravate them because of cellular senescence. Cellular senescence can occur at any life stage, from embryo to adulthood, although it is associated with the aging process [133].…”
Section: Neurodegenerative Diseases In Agingmentioning
confidence: 99%
“…Aged CPCs showed spontaneous osteogenic differentiation and lower chondrogenic differentiation (Chang et al, 2011). In our previously published data, sonic hedgehog, osteogenesis inducer, was highly expressed in OA-CPCs and could induce CPC senescence and chondrocyte apoptosis, which may be used as target and biomarkers for OA (Feng et al, 2021;Liu et al, 2022).…”
Section: Agingmentioning
confidence: 94%
“…Recently, it is reported that overloading promotes chondrocyte senescence, and contributes to OA progression ( Zhang et al, 2022 ). However, physiological mechanical stimulation could upregulate chondrogenic markers in vitro ( Neumann et al, 2015 ), but nuclear factor kappa-B (NFκB) can abolish mechano-induced ECM synthesis ( Luckgen et al, 2022 ). In addition, mechanical loading is also associated with aging that younger animals showed greater plasticity ( Walsh et al, 2020 ).…”
Section: The Influence Of External and Inner Factors On Cpcsmentioning
confidence: 99%
“…Further, MSCs secretome releases several neurotrophic factors, which are all linked to axo-glial regeneration, such as neurotrophin-1 (NT-1), neurotrophin-3 (NT-3), neurotrophin-4 (NT4), ciliary-derived neurotrophic factor (CDNF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), glial cell line-derived neurotrophic factor (GDNF), fibroblast growth factor (bFGF), and ciliary neurotrophic factor (CNTF) [69]. However, recent studies show that cellular aging (i.e., donor age, increased passages, replication stress, telomere deletion, and cellular exhaustion) drives MSCs into senescence phenotype [70,71]. Resulting senescent MSCs are known to exhibit pro-inflammatory effects and impede tissue regeneration [70][71][72].…”
Section: Other Cells and Factors Used For Nerve Tissue Engineering Ap...mentioning
confidence: 99%
“…However, recent studies show that cellular aging (i.e., donor age, increased passages, replication stress, telomere deletion, and cellular exhaustion) drives MSCs into senescence phenotype [70,71]. Resulting senescent MSCs are known to exhibit pro-inflammatory effects and impede tissue regeneration [70][71][72].…”
Section: Other Cells and Factors Used For Nerve Tissue Engineering Ap...mentioning
confidence: 99%